The endorsement of dysfunctional attitudes is associated with an impaired retrieval of specific autobiographical memories in response to matching cues. - Spinhoven, P; Bockting, C; Kremers, I; Schene, A; Mark, J; Williams, G (2007)
Two studies investigated a hypothesis of Dalgleish et al. (2003) that overgeneral memory may arise from matching between task cues and dysfunctional attitudes or schemas. In the first study, 111 euthymic patients with at least two previous major depressive episodes completed the Dysfunctional Attitude Scale: Form A (DAS-A) and the Autobiographical Memory Test (AMT). In the second study, 82 patients with a borderline personality disorder completed the Young Schema Questionnaire (YSQ) and the same version of the AMT. In both studies, patients retrieved less specific autobiographical memories in response to cue words that matched highly endorsed attitudes or schemas. These results suggest that an impaired retrieval of specific memories may be the result of certain cues activating generic, higher-order mental representations.